A DNA tetrahedron-loaded natural photosensitizer with aggregation-induced emission characteristics for boosting fluorescence imaging-guided photodynamic therapy. (1st June 2021) - Zhu, Wei; Ma, Ke; Yan, Zhi-Chao; Wu, Qian; Wang, Dong; Tang, Ben Zhong
Abstract : A natural AIE-active PS (PaH) is utilized to bind into DNA-T for cancer theranostics. The constructed PaH@DNA-T exhibits highly boosted fluorescence intensity and ROS generation, as well as much higher cell uptake efficiency. Abstract : Numerous drug delivery systems have been developed and applied in theranostics due to inherent properties such as functional modification, increased intracellular uptake, and controllable drug release. However, their underlying cytotoxicity still causes safety concerns and limited clinical application. Due to the excellent biocompatibility and cellular permeability, DNA tetrahedron (DNA-T) provides a promising platform to construct prominent drug delivery systems. In this contribution, we employ DNA-T as the carrier for the intracellular delivery of palmatine hydrochloride (PaH), which is a natural photosensitizer (PS) with aggregation-induced emission (AIE) characteristics. By taking advantages of DNA-T binding, the cellular uptake of PaH significantly increases and the PaH transportation efficiency to the nucleus is accelerated by light-driving. The combination of DNA-T and PaH not only enhances the fluorescence intensity but also promotes the photodynamic effects, which are beneficial to cancer diagnosis and treatment. This study thus provides a novel pathway for the theranostics using natural AIE luminogens.